PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS SPARKOL VIDEOSCRIBE PADA PEMBELAJARAN PENDIDIKAN PANCASILA DI KELAS V SEKOLAH DASAR - Gustina, Misra; Erita, Yeni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the suboptimal use of digital technology in producing engaging and contextual learning media for Pancasila Education in elementary schools. This study aims to develop Sparkol Videoscribe learning media for fifth-grade Pancasila Education that is valid, practical, and effective. The research method used is research and development (R&D) with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The research data consists of qualitative data obtained through observation, interviews, and expert validation, and quantitative data obtained from validation results, teacher and student questionnaire responses, and effectiveness testing. The trial was conducted at SDN 36 Cengkeh, with research subjects from SDN 30 Cengkeh and SDN 18 Kampung Baru. The validation results for the material, language, and media showed an average percentage of 92.2%, categorized as very valid. The practicality of the media at the pilot school, SDN 36 Cengkeh, was 89.28% (teachers) and 93.30% (students). At the research school, SDN 30 Cengkeh, it was 96.42% (teachers) and 94.04% (students), while at SDN 18 Kampung Baru, it was 92.85% (teachers) and 96.13% (students), all of which were categorized as very practical. The effectiveness of the media, based on the completeness of learning outcomes, showed a significant increase, with the classical completeness percentage reaching 100% in all three pilot schools. Thus, the Sparkol Videoscribe learning media is declared valid, very practical, and effective for use in fifth-grade Pancasila Education.